(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kerala was devastated by floods, as a result of the abnormal rainfall during the monsoon seasons of 2018 and 2019, resulting in the deposition of vast quantities of flood soil in numerous places around the state. Instead of discarding these accumulated soils, it would be extremely beneficial if they could be utilised as construction materials. In this work, attempts were made to exploit flood deposits for the production of stabilised compression blocks. This study’s purpose is consequently to assess the suitability of the flood deposits for the production of cement stabilised compressed bocks. For the experiment, soil samples were obtained from two distinct locations: Chalakkudy in the district of Thrissur and Anakkal in the district of Palakkad. The compressive strength, water absorption, and weatherability of compressed, cement-stabilized blocks formed from flood-deposited soils were evaluated. The results indicate that flood deposits can be utilised to produce cement stabilised compression blocks.